Portuguese carrageenophytes - Carrageenan composition and geographic distribution of eight species (Gigartinales, Rhodophyta) - Pereira, Leonel (2011)
Eight carrageenophytes from the Centre and North coast of Portugal, representing seven genera and three families of Gigartinales, were studied in 15 different coastal stations in a geographic study, from Baleal (Peniche), in the central zone, to Moledo, in the northern zone. In order to characterize the different carrageenan types, 1HNMRspectroscopy was used to identify and quantify the different carrageenan fractions in the extracted phycocolloids (both water and alkali extractions). Thereby, detailed information concerning the properties and structure of these polysaccharides at molecular level was revealed. Based on the results of the analysis of the carrageenan types, the following conclusions were made: female gametophytes and non-fertile thalli of Chondrus crispus, Mastocarpus stellatus, Chondracanthus teedei var. lusitanicus, Gigartina pistillata, Chondracanthus acicularis and Gymnogongrus crenulatus, presented a varying degrees of kappa–iota hybrid carrageenan (co-polymers of kappa–iota carrageenan). The kappa/iota ratio ranged from 0 to 2.2. The carrageenans extracted from Ahnfeltiopsis devoniensis were mainly iota-carrageenan, but some geographic variations in the composition of carrageenans were found. Calliblepharis jubata contained carrageenans of iota-type in all reproductive stages. Lambda-family carrageenans were found in tetrasporophytes of C. cripus (lambda), M. stellatus (lambda), C. teedei var. lusitanicus (hybrid xi–theta), C. acicularis (hybrid xi–theta) and G. pistillata (hybrid xi–lambda).